Evaluating the contribution of the cause of kidney disease to prognosis in ckd: Results from the Study of Heart and Renal Protection (SHARP) - Haynes, R; Staplin, N; Emberson, J; Herrington, W; Tomson, C; Agodoa, L; Tesar, V; Levin, A; Lewis, D; Reith, C; Baigent, C; Landray, M (2014)
Background The relevance of the cause of kidney disease to prognosis among patients with chronic kidney disease is uncertain. Study Design Observational study. Settings and Participants 6,245 nondialysis participants in the Study of Heart and Renal Protection (SHARP). Predictor Baseline cause of kidney disease was categorized into 4 groups: cystic kidney disease, diabetic nephropathy, glomerulonephritis, and other recorded diagnoses. Outcomes End-stage renal disease (ESRD; dialysis or transplantation) and death. Results During an average 4.7 years' follow-up, 2,080 participants progressed to ESRD, including 454 with cystic kidney disease (23% per year), 378 with glomerulonephritis (10% per year), 309 with diabetic nephropathy (12% per year), and 939 with other recorded diagnoses (8% per year). By comparison with patients with cystic kidney disease, other disease groups had substantially lower adjusted risks of ESRD (relative risks of 0.28 [95% CI, 0.24-0.32], 0.40 [95% CI, 0.34-0.47], and 0.29 [95% CI, 0.25-0.32] for glomerulonephritis, diabetic nephropathy, and other recorded diagnoses, respectively). Albuminuria and baseline estimated glomerular filtration rate were associated more weakly with risk of ESRD in patients with cystic kidney disease than the 3 other diagnostic categories (P for interaction, <0.001 and 0.01, respectively). Death before ESRD was uncommon in patients with cystic kidney disease, but was a major competing risk for participants with diabetic nephropathy, whose adjusted risk of death was 2-fold higher than that of the cystic kidney disease group (relative risk, 2.35 [95% CI, 1.73-3.18]). Limitations Exclusion of patients with prior myocardial infarction or coronary revascularization. Conclusions The cause of kidney disease has substantial prognostic implications. Other things being equal, patients with cystic kidney disease are at much higher risk of ESRD (and much lower risk of death before ESRD) than other patients. Patients with diabetic nephropathy are at particularly high risk of death prior to reaching ESRD. © 2014 by the National Kidney Foundation, Inc.